ICROPM 2020: Crop Modeling for the Future. (15th December 2020) - Hoogenboom, Gerrit; Justes, Eric; Pradal, Christophe; Launay, Marie; Asseng, Senthold; Ewert, Frank; Martre, Pierre
Abstract: During the past decade, the interest in using crop models for research, education, extension, outreach and in the private sector has rapidly increased. The iCROPM 2020 Symposium entitled 'Crop Modeling for the Future', held in February 2020, therefore, provided a great opportunity for over 400 scientists from 50 different countries to exchange information on crop model development, evaluation with experimental data and implementation. A key outcome was the understanding that crop models simulate the dynamics of the soil-plant-atmosphere continuum. Thus, the models can be used for a quantitative and multi-criteria assessment of cropping system functioning, agronomic performance and environmental impact. This should result in more practical applications that can provide actionable information for stakeholders.